Self-power-generation hydrogel stent for 3D printing as well as preparation method and application of self-power-generation hydrogel stent
Prepare self-produced electrohydrogel scaffolds through 3D printing technology, combine zinc and iron powder with double bioink with sodium alginate/gelin hydrogel to build a multi-modular battery hydrogel system, solving the problem of traditional dressings in wound healing The problems of Chinese drug resistance and scar formation have achieved scar-free healing.
Patent Information
- Application Number
- CN202411566256.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Traditional wound dressings face drug resistance and potential tumorigenic problems in promoting wound healing, and are difficult to effectively simulate and enhance endogenous bioelectricity, resulting in delayed healing and scar formation.
A self-produced electrohydrogel scaffold was prepared by 3D printing technology, combining zinc and iron powder with double bioink and sodium alginate/gelin hydrogel, and constructing the cathode and anode through dual nozzles to form a diverse modular The battery hydrogel system simulates endogenous electric fields and releases zinc and iron ions, with antibacterial, anti-inflammatory and pro-angiogenetic effects.
Accelerating scar-free healing of wounds within 16 days is achieved, which is superior to the silicone-based wound dressings on the market, providing long-lasting bioelectric stimulation and multiple repair mechanisms, promoting rapid scar-free healing of wounds.
Smart Images

Figure CN119386258A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical engineering, and in particular to a 3D printed self-generated hydrogel scaffold and a preparation method and application thereof. Background Art
[0002] Skin injuries often show delayed healing and are prone to scarring due to persistent infection, inflammatory infiltration, insufficient vascularization, and oxidative damage. Good wound healing relies on the integrated management of the inflammation, repair, and remodeling phases. Traditional dressings mainly target specific phases of the healing process and rely on biological agents such as antibiotics and growth factors, but often face problems in promoting wound healing, including drug resistance and potential tumorigenicity. Recent studies have shown that methods using physical stimulation (electricity, magnetism, and light) and chemical signals (ions) can effectively regulate the microenvironment of tissue healing, showing the promise of accelerating wound healing and achieving scar-free outcomes.
[0003] As a fundamental property of biological activity, electrical stimulation can dynamically regulate the TGF-β / Smad signaling pathway, thereby promoting cell proliferation, migration, and extracellular matrix remodeling while inhibiting scar formation. However, bioelectricity usually gradually weakens during the physiological healing process, leading to downregulation of genes involved in repair and healing, resulting in disordered collagen fiber deposition and abnormal remodeling of the extracellular matrix. Therefore, the development of new wound dressings that can mimic and enhance endogenous bioelectricity is crucial to accelerate healing and prevent scar formation. Implantable piezoelectric materials provide a way to stimulate endogenous electricity. However, these bioelectric signals usually require force-to-electricity conversion, resulting in unstable and unsustainable signal output. In contrast, biodegradable batteries have attracted widespread attention due to their current stability, high energy density, and ease of use. Enzyme cascade-based biofuel cells (EBFCs) have demonstrated the potential for stable current output and scar-free wound healing, but they face many challenges, including sensitivity to environmental factors (such as temperature and pH), easy inactivation, and high cost, which ultimately hinder their large-scale customization and clinical application.
[0004] Different from the previous self-generated electricity strategy, metal materials such as magnesium, zinc, molybdenum, iron and tungsten are increasingly becoming electrode materials due to their inherent electrochemical potential difference. Existing studies have developed biodegradable batteries based on magnesium anodes. However, due to its very low standard electrode potential (-2.38V vs standard hydrogen electrode), its redox reaction is often more violent, which limits the working time of the battery and often requires frequent dressing changes during practical applications. In contrast, zinc, as a promising anode material, has attracted increasing attention from researchers in recent years. Zinc can exhibit a milder and more stable reaction (its standard electrode potential is -0.76V vs standard hydrogen electrode), which can provide a more continuous current to promote wound healing. In addition, the Zn2+ released by zinc during degradation exhibits significant broad-spectrum antibacterial effects and inherent anti-inflammatory ability by inhibiting the NF-κB signaling pathway, thereby assisting the smooth transition from the inflammatory stage of wound healing to the repair stage and preventing it from developing into chronic wounds. Subsequently, when wound healing enters the repair stage, insufficient angiogenesis can also lead to delayed healing with scars. Iron, as a common cathode material, can form a potential difference with zinc. When degraded, the iron ions released can promote angiogenesis through the HIF-1a / VEGF signaling pathway, thereby accelerating the healing of the wound repair period. Therefore, a zinc-iron biobattery can take advantage of the common advantages of enhancing endogenous electrical stimulation, having antibacterial and anti-inflammatory properties, and promoting angiogenesis, thereby providing sufficient physical stimulation and chemical signals to the damaged area, providing a solution for accelerating scar-free wound healing.
[0005] However, there are several challenges in using metals to construct electrode systems in wound dressings: (1) they cannot provide a suitable living environment for cells at the defect site; (2) they degrade slowly in vivo and are prone to large-scale metal ion precipitation, which has an adverse effect on the wound site; (3) the manufacturing process is complex and requires a diaphragm between the anode and cathode to prevent short circuits. Therefore, there are relatively few reports on metal-based bio-galvanic self-powered wound dressings. To address these challenges, hydrogels can provide a moist environment that is conducive to cell survival and are degradable. More importantly, hydrogels have the properties of both solids and liquids. The solid properties make them function like diaphragms, and the liquid properties can act as electrolytes and promote ion transport. Therefore, the degradable electrode system formed by hydrogels and metal powders can provide an excellent living environment and induction environment for the wound site. However, traditional hydrogel battery production technology usually involves separately manufacturing two electrode materials and then assembling them together, which limits strong bonding, structural stability, and large-scale reproducibility.
[0006] 3D printing technology offers advantages such as rapid manufacturing, personalization, and multi-material integration, providing an excellent strategy for the one-step preparation of battery hydrogels. Among various hydrogels, sodium alginate (SA) stands out due to its unique printability and can be used with Ca2 + cross-linking to form calcium alginate solid electrolyte can not only promote ion transport inside the battery, but also provide a favorable environment for cell survival. At the same time, gelatin (AG), as a denatured hydrolyzate of collagen, exhibits excellent biocompatibility, degradability and cell adhesion sites, thereby providing an optimal environment for cell survival, while enhancing the mechanical properties of SA and regulating its degradability. Therefore, the design of dual bio-ink combining zinc and iron powders with SA / AG (SG) hydrogel and the stacking of cathode and anode by dual nozzle 3D printing provides a promising method for constructing battery hydrogels.
[0007] In addition, the detachment of the dressing during use will also lead to the interruption of the applied physical electrical stimulation and chemical ion signals. In clinical practice, the gold standard for dressing fixation often uses suture fixation, which not only increases trauma, but also makes it easier for scars to form at the suture site. Therefore, the adhesion of new dressings has attracted widespread attention. Polydopamine (PDA) has a similar structure to the adhesive protein of mussels, has excellent adhesion, conductivity and cell affinity, and can promote the transmission of electrical stimulation to the skin defect through the dressing. However, there are difficulties in constructing a printable adhesive hydrogel based on PDA: the carboxyl group of SA can combine with the amino and phenolic hydroxyl groups of PDA, thereby "blocking" certain adhesion sites of polydopamine. In addition, the contact area between the printed hydrogel and the tissue will be reduced. These factors will reduce its overall adhesion. Therefore, it is a better choice to construct a pre-polymerized solution to form an adhesion layer on the surface of the scaffold in situ.
[0008] In summary, the present invention provides a 3D printed, self-produced electrohydrogel scaffold that promotes wound healing. Its multi-module integrates simulated endogenous electric field, antibacterial, anti-inflammatory, angiogenic, free radical scavenging and adhesion properties, which can accelerate wound healing without scars within 16 days, which is superior to silicone-based wound dressings on the market. This represents a pioneering achievement in accelerating scar-free wound healing through metal-based galvanic hydrogels, and provides a revolutionary solution to repair defective tissues based on the physical and chemical signals provided by metal-based galvanic hydrogels. Summary of the invention
[0009] The purpose of the present invention is to provide a 3D printed self-generated hydrogel scaffold, wherein the self-generated hydrogel scaffold comprises an anode scaffold and a cathode scaffold, wherein the anode scaffold is obtained by 3D printing of a hydrogel containing zinc, and the cathode scaffold is obtained by 3D printing of a hydrogel containing iron.
[0010] Preferably, the concentration of zinc and iron in the hydrogel is 0.5% to 1% w / v.
[0011] Preferably, the hydrogel is prepared by adding gelatin into deionized water and then adding sodium alginate.
[0012] Preferably, the outside of the anode support is also wrapped with a prepolymer solution, and the prepolymer solution is prepared from dopamine, ammonium persulfate, N,N'-methylenebisacrylamide, acrylamide and tetramethylethylenediamine.
[0013] Preferably, in the prepolymerization solution, the ratio of dopamine to acrylamide is 0.2-1.2% w / t; the ratio of ammonium persulfate to acrylamide is 10% w / t; the ratio of N,N'-methylenebisacrylamide to acrylamide is 0.12% w / t; and the volume ratio of tetramethylethylenediamine to water solvent is 1:625.
[0014] The second object of the present invention is to provide a method for preparing the self-generated hydrogel scaffold, comprising the following steps: (1) dissolving gelatin in deionized water, adding sodium alginate, and stirring evenly;
[0015] (2) dividing the solution obtained in step (1) into two parts, adding zinc powder and iron powder respectively, and stirring evenly to obtain an anode support material and a cathode support material;
[0016] (3) loading the anode support material and the cathode support material obtained in step (2) into a 3D printing barrel, printing them using a dual-nozzle 3D printing technology, soaking them in a calcium chloride solution, and storing them overnight to obtain an anode support and a cathode support;
[0017] (4) dissolving dopamine in an alkaline aqueous solution and stirring until the solution turns brown;
[0018] (5) adding ammonium persulfate, N,N'-methylenebisacrylamide, acrylamide, and tetramethylethylenediamine to the solution obtained in step (4) in an ice bath to form a brown prepolymer solution;
[0019] (6) Pour the solution obtained in step (5) into the mold, immerse one end of the anode bracket obtained in step (3) in the mold, and place it in an oven at 60° C. for 30 minutes to form an adhesive ZFBH bracket.
[0020] Preferably, the reaction in step (1) is carried out under heating conditions, the mass volume ratio of the zinc powder or iron powder in step (2) to deionized water is 0.5%-1% (w / v); and the concentration of the calcium chloride solution in step (3) is 2% (w / v).
[0021] Preferably, the pH value of the alkaline aqueous solution in step (4) is 12.
[0022] The third object of the present invention is to provide the self-generated hydrogel scaffold, or the use of the self-generated hydrogel scaffold prepared by the preparation method in the preparation of skin repair materials and tissue engineering.
[0023] The fourth object of the present invention is to provide the self-generated hydrogel scaffold, or the use of the self-generated hydrogel scaffold prepared by the preparation method in the preparation of dressings for treating skin injuries.
[0024] The beneficial effects of the present invention are: (1) The present invention adopts direct writing 3D printing technology to prepare a self-produced hydrogel scaffold with excellent biocompatibility, stable and long-lasting voltage output, and excellent wound healing effect without scars; it provides a suitable living environment and induction environment for cells in the wound healing site, simulates and amplifies endogenous electrical stimulation, cascade regulates the expression of genes related to wound repair, reduces the expression of pro-inflammatory factors and accelerates vascularization of the wound site, thereby promoting scarless wound healing.
[0025] (2) The self-produced hydrogel scaffold prepared by the present invention adopts the dual properties of solid and liquid of hydrogel. Based on the solid properties, it plays a function similar to that of a battery separator, and based on the liquid properties, it acts as an electrolyte and promotes ion transport, effectively solving the problem of complex structure of traditional batteries caused by the need to construct a separator.
[0026] (3) The self-generated hydrogel scaffold prepared by the present invention has multiple repair mechanisms such as physical stimulation and chemical stimulation, including the release of zinc ions to exert anti-inflammatory effects, the release of iron ions to promote angiogenesis, the excellent antioxidant properties of each component unit, and the continuous generation of bioelectricity to promote tissue remodeling, thereby achieving scar-free wound healing, effectively avoiding the shortcomings of traditional dressings such as single function and low effect.
[0027] (4) The self-generated hydrogel scaffold prepared by the present invention constructs an adhesion layer at one end close to the wound, which prevents the dressing from falling off during use and exerts long-lasting bioelectric stimulation.
[0028] (5) The self-produced hydrogel scaffold prepared in the present invention is based on the 3D printing additive manufacturing method, which is easy to be produced quickly, in batches, on a large scale, and in a personalized manner. It has broad market prospects in the field of skin tissue repair and provides a new treatment solution for accelerating scar-free wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The present invention will be described in further detail below in conjunction with the accompanying drawings.
[0030] Figure 1 A physical picture of the ZFBH bracket of the present invention
[0031] Figure 2 Characterization of the gelation and adhesion properties of the PDM hydrogel of the present invention
[0032] Note: (A) Gel formation characteristics; (B) Adhesion mechanics; (C) Adhesion pictures
[0033] Figure 3 Figures and microstructure characterization of the ZFBH scaffold of the present invention: (A) Low magnification SEM of FeH scaffold; (B) Low magnification SEM of ZnH scaffold; (CD) Element distribution of FeH scaffold and ZnH scaffold; (EF) Local magnification SEM of FeH scaffold and ZnH scaffold; (GH) XRD characterization of FeH scaffold and ZnH scaffold; (I) SEM of cross section of ZFBH scaffold; (JK) Element distribution of ZFBH scaffold; (L) XRD characterization of ZFBH scaffold
[0034] Figure 4 This is a performance characterization diagram of the ZFBH stent of the present invention;
[0035] Note: (A) electrical properties; (B) free radical scavenging performance
[0036] Figure 5 This is a test diagram of the biocompatibility and cell migration ability of the ZFBH scaffold of the present invention;
[0037] Note: (A) CCK-8; (B) Live / dead cell staining; (C) Hemolysis assay; (D) Scratch assay
[0038] Figure 6 The mechanism of the ZFBH scaffold of the present invention in promoting wound healing in vitro;
[0039] Note: (A) Evaluation of antibacterial properties; (B) RT-qPCR evaluation of the expression of genes related to repair, inflammation, and angiogenesis
[0040] Figure 7 The images of the ZFBH scaffold of the present invention accelerating scarless healing and H&E, Masson, COL-I, and COL-III slices. Note: (A) Wound healing photos; (B) Wound area quantification; (C) H&E and Masson staining; (D) Collagen quantification; (E) COL-I and COL-III staining images; (F) Quantitative analysis of COL-I and COL-III
[0041] Figure 8 This is the histochemical section diagram of TGF-β, Smad3 and α-SMA of the ZFBH scaffold of the present invention.
[0042] Note: (A) Representative staining images of TGF-β, Smad3 and α-SMA; (B) Quantitative analysis of TGF-β, Smad3 and α-SMA
[0043] Fig. 9 This is the histochemical section diagram of TNF-α and IL-10 of the ZFBH scaffold of the present invention.
[0044] Note: (A) Representative staining images of TNF-α and IL-10; (B) Quantitative analysis of TNF-α and IL-10
[0045] Fig.10 This is a histochemical section diagram of CD31 of the ZFBH scaffold of the present invention.
[0046] Note: (A) Representative staining images of CD31; (B) Quantitative analysis of CD31
[0047] Fig.11 This is a slice for visceral toxicological evaluation of the ZFBH stent of the present invention.
[0048] Note: The figure shows representative H&E staining images of the heart, liver, spleen, lung, and kidney in the Control group and ZFBH scaffold group Fig.12 Simulation diagram of the scheme of the present invention DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] In the following examples, unless otherwise specified, the methods used are conventional methods and can be obtained from the literature;
[0051] In the following embodiments, unless otherwise specified, the consumables used can be purchased from the market.
[0052] Example 1. Preparation of SG scaffold
[0053] (1) Gelatin (3 g) was dissolved in deionized water (100 mL) at 50 °C in a water bath, followed by the addition of sodium alginate (6 g) and stirring;
[0054] (2) loading the mixture obtained in step (1) into a 3D printing barrel and printing with a 3D printer;
[0055] (3) After printing is completed, the sample obtained in step (3) is immersed in a calcium chloride solution (2% w / v) and stored overnight to obtain the SG scaffold.
[0056] Example 2. Preparation of FeH scaffold
[0057] (1) Gelatin (3 g) was dissolved in deionized water (100 mL) at 50 °C in a water bath, followed by the addition of sodium alginate (6 g) and stirring;
[0058] (2) adding iron powder (1 g) to the hydrogel obtained in step (1) and stirring evenly;
[0059] (3) loading the mixture obtained in step (2) into a 3D printing barrel and printing with a 3D printer;
[0060] (4) After printing is completed, the sample obtained in step (3) is immersed in a calcium chloride solution (2% w / v) and stored overnight to obtain a FeH scaffold.
[0061] Example 3: Preparation of ZnH scaffold
[0062] (1) Gelatin (3 g) was dissolved in deionized water (100 mL) at 50 °C in a water bath, followed by the addition of sodium alginate (6 g) and stirring;
[0063] (2) adding zinc powder (1 g) to the hydrogel obtained in step (1) and stirring evenly;
[0064] (3) loading the mixture obtained in step (2) into a 3D printing barrel and printing with a 3D printer;
[0065] (4) After printing is completed, the sample obtained in step (3) is immersed in a calcium chloride solution (2% w / v) and stored overnight to obtain a ZnH scaffold.
[0066] Example 4. Preparation of PAM hydrogel
[0067] (1) ammonium persulfate (0.05 g), N,N'-methylenebisacrylamide (0.003 g), acrylamide (2.5 g), and tetramethylethylenediamine (20 μL) were sequentially added to 12.5 mL of deionized water under an ice bath to form a transparent prepolymer solution;
[0068] (2) Pour the solution obtained in step (1) into a mold and place it in an oven at 60° C. for 30 min to form a PAM hydrogel.
[0069] Example 5. Preparation of PDM hydrogel
[0070] (1) Different masses of dopamine (0.005 g, 0.01 g, 0.02 g and 0.03 g) were dissolved in 12.5 mL of alkaline (pH = 12) aqueous solution and stirred for 20 min. The solution gradually turned brown.
[0071] (2) ammonium persulfate (0.25 g), N,N'-methylenebisacrylamide (0.003 g), acrylamide (2.5 g), and tetramethylethylenediamine (20 μL) were added to the solution obtained in step (1) in an ice bath to form a brown prepolymer solution;
[0072] (3) Pour the solution obtained in step (2) into the mold and place it in an oven at 60°C for 30 minutes to form an adhesive PDM hydrogel. According to the different mass ratios of dopamine / acrylamide, they can be named 0.2% PDM, 0.4% PDM, 0.8% PDM and 1.2% PDM.
[0073] Example 6. Preparation of ZFBH Scaffold
[0074] (1) Gelatin (6 g) was dissolved in deionized water (200 mL) at 50°C in a water bath, followed by the addition of sodium alginate (12 g) and stirring;
[0075] (2) The solution obtained in step (1) was divided into two parts, and iron powder (1 g) and zinc powder (1 g) were added respectively, and stirred evenly;
[0076] (3) loading the mixture obtained in step (2) into a 3D printing barrel and printing using a dual-nozzle 3D printing technology;
[0077] (4) After printing is completed, the sample obtained in step (3) is immersed in a calcium chloride solution (2% w / v) and stored overnight to obtain a ZnH scaffold and a FeH scaffold;
[0078] (5) Dopamine (0.02 g) was dissolved in an alkaline aqueous solution (pH = 12) and stirred for 20 min. The solution gradually turned brown.
[0079] (6) under ice bath, the solution obtained in step (5) was added with ammonium persulfate (0.25 g), N,N'-methylenebisacrylamide (0.003 g), acrylamide (2.5 g), and tetramethylethylenediamine (20 μL) in sequence to form a brown prepolymer solution;
[0080] (7) Pour the solution obtained in step (6) into the mold, immerse one end of the ZnH scaffold obtained in step (4) into the mold, and place it in an oven at 60°C for 30 minutes to form an adhesive ZFBH scaffold. The preparation process and principle are as follows Fig.12 shown.
[0081] Example 7. Gelation and Adhesion Properties of PAM Hydrogel and PDM Hydrogel
[0082] In this experiment, the PAM of Example 4 and the PDM hydrogels of different concentrations in Example 5 were used as experimental objects for the following experiments: the prepolymerized solutions were poured into glass bottles, placed at 60°C for 30 minutes, and the glass bottles were inverted to observe whether they were gelled. At the same time, the prepolymerized solution was poured into a square mold with a length of 10 mm, a width of 5 mm, and a thickness of 1 mm, and placed at 60°C for 30 minutes for cross-linking. The samples were adhered to pig skin, and the adhesion properties of different PAM hydrogels and PDM hydrogels were evaluated by a universal mechanical testing machine (AGS-X5KN, Shimadzu, Japan). The adhesion characteristics of PDM to different material surfaces were also evaluated.
[0083] Figure 1 A is the gelling performance evaluation of the scaffolds prepared in Examples 4 and 5. As can be seen from the figure, except for 1.2% PDM, the other hydrogels of various concentrations all achieved gelling. Subsequently, the PAM hydrogel, 0.2% PDM, 0.4% PDM, and 0.8% PDM gels were subjected to a tensile test on pig skin. The results showed that the 0.8% PDM gel had the best adhesion performance ( Figure 1 B), it was confirmed that the introduction of dopamine can enhance the adhesion performance of the composite system, and when the concentration is less than or equal to 0.8%, its adhesion performance is positively correlated with the concentration. Therefore, the optimal concentration of 0.8% PDM was selected for subsequent experiments. At this concentration, the hydrogel has excellent adhesion properties and can adhere to the surfaces of various objects such as plastic, glass, ear wash bulbs, weights, etc. ( Figure 1 C).
[0084] Example 8. Microscopic Characterization of FeH Scaffold, ZnH Scaffold and ZFBH Scaffold
[0085] In this experiment, the FeH scaffold, ZnH scaffold, and ZFBH scaffold in Implementation 2, 3, and 6 were used as experimental objects for the following experiments: the structural morphology of the printed hydrogel scaffold was observed, and the printed scaffold was freeze-dried and the morphology of the hydrogel scaffold was observed by scanning electron microscopy (SEM, JEOL JSM-6701F). The gel sample was freeze-dried and ground into powder, and X-ray diffraction (XRD, Rigaku D / Max-2400 diffractometer, CuKα radiation and graphite monochromator, ) were used to characterize the structure and phase composition of the synthesized samples.
[0086] The actual picture of the FeH bracket prepared in Example 2 is as follows Figure 2 A shows the actual image of the ZnH stent prepared in Example 3. Figure 2 B shows the actual image of the ZFBH bracket prepared in Example 6. Figure 2As shown in C, it can be seen from the figure that the color of the ZnH scaffold is silvery white; the color of the FeH scaffold is black; the ZFBH scaffold has a double-layer structure of silvery white and black, and has a layer of brown structure (PDM) on the surface of the silvery white layer (ZnH scaffold).
[0087] Figure 3 The microscopic characterization of the FeH scaffold, ZnH scaffold and ZFBH scaffold prepared in Example 2, Example 3 and Example 6. Under low magnification SEM, Figure 3 The FeH scaffold shown in A and Figure 3 The ZnH scaffolds shown in B all show good morphology without collapse. Through EDS mapping test, it can be detected that Fe and Zn elements are evenly distributed in the FeH scaffolds ( Figure 3 C) and ZnH scaffolds ( Figure 3 D), it is confirmed that the metal powder can be evenly distributed in the bracket. It is worth noting that Figure 3 In the ZnH scaffold shown in B, it can be observed that PDM fills the scaffold and forms many micropores. EDS mapping confirms that the Zn element is distributed in the main body of the scaffold ( Figure 3 D).
[0088] After further magnification, micron-sized particles can be observed on the surface of FeH and ZnH scaffolds, respectively. Figure 3 EF). XRD analysis confirmed that the FeH scaffold had characteristic peaks at 44.7°, 65.0° and 82.3°, corresponding to the (110), (200) and (211) crystal planes of Fe, respectively. Figure 3 G). In contrast, the ZnH scaffold exhibits characteristic peaks at 36.3°, 39.0°, and 43.2°, corresponding to the (002), (100), and (101) crystal planes of Zn, respectively ( Figure 3 H), which is consistent with the standard PDF card. These findings suggest the formation of various metal microelectrode structures throughout the SG scaffold hydrogel electrolyte.
[0089] Figure 3 The cross-sectional SEM results shown in I show that the ZFBH scaffold has a porous structure that can provide channels for cell migration. Figure 3 The EDS mapping results shown by JK clearly show the distribution characteristics of the elements in the scaffold material. According to the image, the iron element is mainly concentrated in the upper layer of the scaffold, while the zinc element is more distributed in the lower layer of the scaffold. The arrangement of these two elements corresponds to the cathode layer and the anode layer of the scaffold. Therefore, it is confirmed that the integrated construction of the ZFBH scaffold can be achieved through the application of dual-nozzle 3D printing technology. In addition, the XRD results confirmed that the ZFBH scaffold showed characteristic peaks of Fe and Zn consistent with the standard PDF card ( Figure 3L). In conclusion, a porous hydrogel formed by Zn and Fe was characterized by microstructure, wherein the upper layer was a Fe electrode and the lower layer was a Zn electrode integrated with PDM-adhesive hydrogel, and there was a seamless connection between them.
[0090] Example 9: Electrical properties of ZFBH bracket
[0091] In this experiment, the PAM, PDM and ZFBH scaffolds in Implementation 4, 5 and 6 were used as implementation objects for the following experiments: The gel samples were encapsulated with high-purity copper foil, copper wires were led out from the cathode and anode, and immersed in 100 mL PBS buffer. It was connected to a high-precision multimeter, and the effective output voltage at different times (0h, 12h, 24h, 72h, 168h) was measured and recorded. In addition, PAM and PDM were used as implementation objects, and electrochemical impedance spectroscopy (EIS) measurements were performed using an electrochemical workstation (760E, CHI), with a scanning frequency range of 100kHz to 0.1Hz and an open circuit potential of 0.1V. The hydrogel with a length of 8mm, a width of 9mm and a thickness of 2mm was placed between two platinum electrodes (10mm×10mm) in a custom quartz cuvette, surrounded by PBS buffer solution. An Ag / AgCl electrode (containing 3M KCl) was used as a reference electrode.
[0092] Figure 4 A i is the voltage output characterization of the ZFBH scaffold prepared in Example 6. It can be seen that the voltage can be stabilized at about 0.45V, 0.35V, 0.28V, 0.21V and 0.12V at 0h, 12h, 24h, 72h and 168h, respectively, confirming that it can meet the long-lasting electrical stimulation for at least 7 days. In addition, among the hydrogel properties required for constructing the ZFBH scaffold, conductivity is the key to transmitting electrical stimulation to skin tissue.
[0093] Figure 4 A ii-iii is the impedance performance test of the hydrogel. The results of Bode plot and Nyquist plot confirm that due to the introduction of dopamine PDA, PDM has lower impedance and higher ionic conductivity compared with PAM, which indicates that PDM has excellent conductivity and can reduce the interface resistance between the ZFBH scaffold and skin tissue.
[0094] Example 10, free radical scavenging ability characterization diagram
[0095] This experiment will implement the SG scaffold, FeH scaffold, ZnH scaffold, PDM hydrogel, and ZFBH scaffold in 1, 2, 3, 5, and 6 as experimental objects for the following experiments:
[0096] (1) Hydroxyl radical detection: Prepare 1.8 mM FeSO4 aqueous solution, 1.8 mM salicylic acid-ethanol / water solution, 1.8 mM salicylic acid-water solution and 0.03% H2O2 solution for use. Mix 2 mL of 1.8 mM FeSO4 aqueous solution, 1.5 mL of 1.8 mM salicylic acid-ethanol solution and 0.1 mL of 0.03% H2O2 solution, add 0.1 g of hydrogel sample and react at 37°C for 30 min. Use a UV spectrophotometer to perform full-band scanning and record the absorbance value of each group of samples at a wavelength of 510 nm.
[0097] Hydroxyl radical scavenging rate = [A0-(A x -A x0 )] / A0*100%
[0098] Note: A0 is the absorbance of the blank control (no sample, color developer H2O2); Ax is the absorbance with sample and H2O2; Ax0 is the absorbance without sample and color developer (H2O2).
[0099] (2) DPPH scavenging ability test: 100 μL of 0.1 mmol / mL DPPH-ethanol solution was mixed with 0.1 g of hydrogel sample and reacted in the dark at room temperature for 30 min. The sample was then centrifuged at 5000 rpm for 5 min to precipitate the hydrogel material. A full-band scan was performed using an ultraviolet spectrophotometer, and the absorbance value of each group of samples at a wavelength of 517 nm was recorded.
[0100] DPPH clearance rate (%) = (1-A t / A0)×100%
[0101] Note: A t and A0 are the absorbance of the test group and the blank group measured at 517 nm, respectively.
[0102] (3) ABTS scavenging ability test: 0.3 g of ABTS diammonium salt was dissolved in 80 mL of deionized water as liquid a, and 0.025 g of the solution was dissolved in 80 mL of deionized water as liquid b. Liquid a and liquid b were mixed and oxidized in the dark for 12 hours. When used, it was diluted 30 times and mixed with 0.1 g of the hydrogel sample. The reaction was carried out for 30 minutes. The full-band scan was performed using an ultraviolet spectrophotometer, and the absorbance value of each group of samples at a wavelength of 734 nm was recorded.
[0103] ABTS clearance rate (%) = (1-A t / A0)×100%
[0104] Note: A t and A0 are the absorbance of the test group and the blank group measured at 734 nm, respectively.
[0105] Figure 4 B is the free radical scavenging rate test of SG scaffold, FeH scaffold, ZnH scaffold, PDM, and ZFBH scaffold in implementation 1, 2, 3, 5, and 6. It can be seen from the figure that the generation of hydroxyl radicals can be enhanced simply by external electrical stimulation, but it depends on Zn and Fe as reducing agents and the antioxidant capacity of PDA. The scavenging efficiency of OH, DPPH, and ABTS of the ZFBH scaffold is 88.6%, 92.0%, and 91.6%, respectively, which can be attributed to the combined effect of the accelerated reaction of the Zn-Fe electrode and PDM. It shows that the ZFBH scaffold exhibits a strong antioxidant capacity, confirming that the hydrogel is expected to eliminate reactive oxygen species (ROS) and reactive nitrogen species (RNS) at the wound site and provide a suitable microenvironment for wound healing.
[0106] Example 11, CCK-8 experiment
[0107] In this experiment, the SG scaffold, PDM, and ZFBH scaffold in Examples 1, 5, and 6 were used as the implementation objects for the following experiments: several groups of gel samples of similar size were prepared in advance, and the samples were thoroughly disinfected and sterilized by ultraviolet (UV) irradiation. The ZFBH scaffold was set with a concentration gradient of 0.5% w / v, 1% w / v, and 2% w / v. L929 cells were used to perform CCK-8 tests on 24-well plates for 1, 3, 5, and 7 days. 1×10 4 Cells were co-cultured with the samples. After a fixed number of days of culture, an appropriate amount of MTT reagent was added and incubated at 37°C for 4 hours. The supernatant was discarded and dimethyl sulfoxide was added to dissolve the purple formazan crystals. At room temperature, the well plate was shaken on a shaker for 15 minutes to dissolve the crystals evenly. The liquid in the 24-well plate was then transferred to a 96-well plate. The absorbance value at OD 450nm was measured by an ELISA reader. Three replica wells were set up for each group.
[0108] Figure 5 A is the CCK-8 cell compatibility test of the SG scaffold, PDM, and ZFBH scaffold in implementation 1, 5, and 6. The results show that the cell viability of the SG scaffold and PDM is greater than 85% at 1, 3, 5, and 7 days, which meets the cell compatibility requirements. The ZFBH scaffold cannot meet the biocompatibility requirements at a concentration of 2%. The 1% ZFBH scaffold has excellent activity in promoting cell proliferation compared to the blank group and the SG scaffold group, which can be attributed to the generation of microcurrent. Therefore, the ZFBH scaffold with an optimal concentration of 1% was selected for subsequent experiments.
[0109] Example 12: Calcein-AM / PI live / dead cell staining
[0110] In this experiment, the SG scaffold, FeH scaffold, ZnH scaffold, PDM, and ZFBH scaffold in Examples 1, 2, 3, 5, and 6 were used as the implementation objects for the following experiments: the cell culture and material disinfection steps were the same as above. 1×10 4 cells and co-cultured with the material for 1, 3, 5 and 7 days. The supernatant was then discarded and washed with PBS buffer. Calcein-AM / PI live / dead cell staining detection kit was used and placed in a 37°C incubator for staining for 0.5 hours. The staining solution was aspirated to terminate the incubation. An appropriate amount of PBS buffer was added to each well to cover the cells. The live cells (yellow-green fluorescence) and dead cells (red fluorescence) were then observed with an inverted fluorescence microscope and photographed.
[0111] Live / dead cell staining is used to observe the survival status of cells after CCK-8 method, such as Figure 5 As shown in B, almost no dead cells labeled with red fluorescence were observed. In addition, the ZFBH scaffold hydrogel has a more excellent ability to promote cell proliferation, and its cell morphology is better, meeting the cell compatibility requirements.
[0112] Example 13, hemolysis experiment
[0113] In this experiment, the SG scaffold, FeH scaffold, ZnH scaffold, PDM, and ZFBH scaffold in Examples 1, 2, 3, 5, and 6 were used as implementation objects for the following experiments: Take an appropriate amount of healthy SPF rat whole blood, add 3.8wt% sodium citrate-normal saline solution thereto, and dilute it with normal saline at a volume ratio of 4:5 for standby use. Place the sample in 10mL normal saline and incubate at 37°C for 30min. Then add 0.2mL diluted blood and culture for 1 hour. Normal saline and deionized water were used as negative control group and positive control group, respectively. Centrifuge all test tubes at 1000rpm for 5 minutes. Transfer the supernatant to a 96-well plate. Read the absorbance (optical density, OD) at a wavelength of 545nm using an ELISA reader to calculate the hemolysis rate.
[0114] Figure 5 The hemolysis experiment shown in C also confirmed that the hemolysis rates of all groups were lower than 5%, meeting the requirements of international standards (ISO standard number: 10993-4), indicating good blood safety.
[0115] Example 14: Scratch test
[0116] This experiment uses the SG scaffold, FeH scaffold, ZnH scaffold, PDM, and ZFBH scaffold in Examples 1, 2, 3, 4, and 5 as the implementation objects for the following experiments: cells are inoculated using a six-well plate, and then the scaffold is co-cultured with the cells. After the cell spreading area reaches 90%, the plate is scratched with a 20 μL pipette tip, rinsed twice with PBS, and then replaced with serum-free basal medium to eliminate the effect of cell proliferation on the experiment. Under the same conditions, the same microscope (Nikon ECLIPSE80i / DS-Ri2 / NIS-ElementsD, Nikon, Japan) is used to observe the changes in the scratch area at 0h, 24h, and 48h and take pictures.
[0117] Figure 5 In D, the effect of ZFBH scaffold on cell migration was investigated using a wound scratch test, with a wire device generating microcurrent. No significant difference was observed in the cell migration distance between the control and PDM groups. However, the cell migration distance of the FeH and ZnH scaffolds increased to a certain extent, which can be attributed to the improvement of cell migration ability due to ion release. The cell migration distance of the ZFBH scaffold group increased significantly at the 24h mark, and the scratch was completely healed at 48h. This indicates that the microcurrent and ion release of the ZFBH scaffold can significantly enhance the migration of L929 and accelerate wound healing.
[0118] Example 15, Antibacterial Experiment
[0119] In this experiment, the SG scaffold, FeH scaffold, ZnH scaffold, PDM, and ZFBH scaffold in Examples 1, 2, 3, 5, and 6 were used as the implementation objects for the following experiments: Escherichia coli and Staphylococcus aureus were inoculated into Luria Bertani medium, cultured on an orbital shaker at 37°C and 200 rpm for 12 h, and then centrifuged to collect the bacteria. The hydrogel sample was cut into a circle with a diameter of about 1 cm, and then placed in a container containing 10 mL of bacterial suspension (10 5 -10 6 CFU / mL) in a sterile centrifuge tube. Shake the centrifuge tube for 30 min at 37°C using a shaker, then take out 100 μL of the suspension and mix it with 20 mL of agar medium. After culturing at 37°C for 12 h, count the total number of colonies appearing on the culture plate. Take three parallel samples for each experimental group.
[0120] Figure 6The results of A showed that the antibacterial effects were in the order of PDM < FeH scaffold < ZnH scaffold < ZFBH scaffold. It was found that PDA could disrupt the structural integrity of bacterial cell membranes through protein chelation and electrostatic effects. The antibacterial effect of the FeH scaffold involved increased membrane permeability, loss of proton energy, leakage of cell contents, and disruption of DNA replication. In addition, the antibacterial effect of the ZnH scaffold was stronger, which could be attributed to the release of Zn 2+ that could interfere with metalloproteins, resulting in protein dysfunction and bacterial cell instability. The inhibition rate of bacteria in the ZFBH scaffold group was close to 100%, which could be attributed to the synergistic effect of the above-mentioned multiple components, achieving the optimal antibacterial effect. Therefore, in this study, the antibacterial efficacy relied on the release of natural ions and electrical stimulation, effectively alleviating the disadvantages brought by antibiotic resistance.
[0121] Example 16, RT-qPCR
[0122] In this experiment, the SG scaffolds, FeH scaffolds, ZnH scaffolds, PDM, and ZFBH scaffolds in Examples 1, 2, 3, 5, and 6 were used as the subjects for the following experiments: The L929 cell line (Shanghai Fusheng Industrial Co., Ltd., X120311) was seeded into 24-well plates at a density of 20,000 cells / well and co-cultured in DMEM medium for 3 days to detect the expression of TGF-β and Smad3 genes. The RAW264.7 cell line (Hunan Fenghui Biotechnology Co., Ltd., CL0266) was used to analyze the expression of TNF-α and IL-10 genes. The HUVEC cell line (ScienCell Research Laboratories, Cat.#8000) was used to detect the expression of HIF-1α and VEGF genes. The cells were digested to ensure that the number of cells in each group was not less than 1×10 6 cells. RNA was extracted from the cells and the total RNA concentration was measured. Subsequently, cDNA was generated by reverse transcription for amplifying the target genes, and then qPCR reactions were performed to calculate the mRNA expression levels.
[0123] Figure 6 The results of B showed that the ZFBH scaffold could activate the TGF-β / Smad3 signaling pathway in vitro ( Figure 6 B i); it could down-regulate the expression of the pro-inflammatory gene TNF-α and up-regulate the expression of the anti-inflammatory gene IL-10 ( Figure 6 B ii); and it could promote the expression of angiogenesis-related genes depending on the HIF-1α / VEGF signaling pathway ( Figure 6 B iii). It was confirmed that the ZFBH scaffold group showed the most prominent up-regulation of repair genes and significant effects on inflammation regulation and angiogenesis ( Figure 6 B iv).
[0124] Example 17: Evaluation of the healing effect of ZFBH scaffold on wounds
[0125] With the approval of the Animal Ethics Committee, several healthy SPF rats were selected to study the ability of various hydrogels to promote the healing of full-thickness skin defect wounds. Rats were anesthetized by intraperitoneal injection of 10% urethane (10% urethane / rat body weight = 0.4 mL / 100 g). Two circular full-thickness wounds (1.0 cm in diameter) were implemented on the back of each mouse. The surface of the surgical wound was covered with hydrogel. Mice were anesthetized with excessive urethane on the 4th, 7th, 14th and 16th days, and the wounds were photographed at the same time. The wound size measured by ImageJ was used to calculate the percentage of wound reduction. The wound and adjacent normal skin were then excised, fixed with 4% paraformaldehyde, and after gradient dehydration, paraffin embedding and sectioning, H&E staining, Masson staining and immunohistochemical staining (COL-I, COL-III) were performed, and observed under an optical microscope, and the healing status and indicators of the defective tissue were analyzed and evaluated.
[0126] like Figure 7 As shown in the figure, in order to explore the effect of ZFBH scaffold dressing on wound healing, we established a full-thickness skin defect model with a diameter of 1 cm on the back of SPF rats. In the animal experiment, the main focus was on the effect of the dressing itself. Adhesive PDM hydrogels were constructed at the bottom of all hydrogels to achieve "suture-free" fixation of the dressing. Figure 7 As shown in AB, on the 4th and 7th days of wound healing, both the FeH scaffold and the ZnH scaffold significantly accelerated wound healing compared with the blank group and the silicone-based dressing group (MS), indicating that the ions released by the metal hydrogel played a key role in promoting wound healing. However, on the 14th and 16th days, the healing effect of the FeH scaffold group was comparable to that of the blank group and the MS group, indicating that it mainly promoted early wound healing, but the scar remodeling ability was limited, which may be due to the excessive proliferation of collagen and blood vessels caused by the release of iron ions. In contrast, the surface healing of the ZnH scaffold group was smoother, and there was a trend of reduced scars. In addition, the ZFBH scaffold group had the strongest healing ability, achieving complete healing on the 14th day and scar-free healing on the 16th day, which means that the galvanic cell reaction composed of the two metals played a more significant role in promoting wound healing, which was significantly better than the silicone-based wound dressing (MS group) on the market.
[0127] Wound healing was assessed by H&E staining ( Figure 7C). At day 4 of skin healing, all groups showed similar healing processes, including granulation tissue infiltration and a pronounced inflammatory response. The ZnH scaffold group showed a milder inflammatory response compared to the FeH scaffold group, while the MS group had the most pronounced inflammatory response. By day 7, the number of inflammatory cells and the discontinuous epidermis were significantly reduced in all groups. Notably, the FeH scaffold group showed a stronger vascularization capacity compared to the ZnH scaffold group. By day 16, all groups had a continuous epithelium and skin appendages, but there were great differences in histology, especially epithelial thickening was observed in the FeH scaffold group. In contrast, the ZFBH scaffold group showed beneficial anti-inflammatory and vascular effects in the early stage, and transitioned to tissue remodeling in the later stage, with a more complete epithelium and increased formation of hair follicle structures, thus meeting the morphological and functional requirements of skin tissue healing.
[0128] Subsequently, Masson staining and the corresponding quantitative analysis of collagen showed that the content of collagen continued to increase over time. During the wound healing stage, the collagen content of the ZnH scaffold, FeH scaffold, and ZFBH scaffold groups was always superior to that of the Control group and the MS group ( Figure 7 D). Compared with the two metals, the ZnH scaffold group showed higher collagen content on day 4, which can be attributed to the ZnH scaffold, while the FeH scaffold group reached the highest level on day 7. This observation suggests that the two hydrogels play different roles in the inflammatory and repair phases of wound healing, thereby effectively promoting collagen deposition and accelerating the tissue repair process. It is worth mentioning that due to the introduction of electrical stimulation, the ZFBH scaffold hydrogel group reached the highest level of collagen deposition on days 4 and 7. By day 16, the expression of collagen content was not significant, but showed a more orderly arrangement, which can be attributed to collagen remodeling, which is more beneficial for scar-free healing.
[0129] The collagen fibers in the skin are mainly composed of type I collagen (COL-I) and type III collagen (COL-Ⅲ), of which COL-I is relatively thick and plays an important role in maintaining the hardness and firmness of the skin. However, excessive COL-I may cause skin stiffness and form scars after wound healing. Relatively speaking, COL-Ⅲ is the main component of skin reticular fibers. The higher its content, the thinner the fiber bundles, and the more delicate and smooth the skin tissue appears. Therefore, in order to further evaluate the effect of ZFBH scaffolds in scar-free healing, we performed immunohistochemistry (IHC) staining on the 16th day to evaluate the expression of COL-I and COL-III. The results showed that compared with other groups, the expression of COL-I in the ZFBH scaffold group was significantly reduced, while the expression of COL-III was increased, and the ratio of COL-I to COL-III was closer to the level of normal skin ( Figure 7EF). This finding supports the view that the healing process of the ZFBH scaffold group is more inclined to scarless healing, and its healing mechanism includes accelerating the initial rapid healing and promoting the subsequent ECM remodeling.
[0130] Example 18: Study on the mechanism of ZFBH scaffold promoting wound healing
[0131] Wound healing can be roughly divided into three stages: inflammation, repair, and remodeling. In order to explore the mechanism of ZFBH scaffold in promoting scarless wound healing, the expression of repair-related proteins (TGF-β, Smad3, α-SMA), inflammation-related proteins (TNF-α, IL-10), and angiogenesis-related proteins (CD31) were evaluated by IHC staining.
[0132] In the process of wound healing, the TGF-β / Smad3 / α-SMA signaling pathway plays a key role in wound healing and scar formation. Figure 8 As shown in IHC staining and related quantitative analysis shown in AB, the ZFBH scaffold had the highest expression of related proteins on the 4th and 7th days, but its expression decreased significantly on the 16th day. This shows that the ZFBH scaffold based on bioelectric stimulation can upregulate the TGF-β / Smad3 / α-SMA signaling pathway during the inflammatory and proliferative phases of wound healing, promote the rapid proliferation of fibroblasts, and accelerate initial healing, thereby shortening the overall healing time. In addition, the significant reduction of these markers in the remodeling phase helped prevent the excessive proliferation of fibroblasts, thereby minimizing the risk of scar formation. This result confirms that the ZFBH scaffold enhances the dynamic regulation ability of the TGF-β / Smad3 / α-SMA signaling pathway, promotes accelerated wound healing, and ensures scar-free recovery.
[0133] Inflammatory factors play a key role in regulating the immune microenvironment during wound healing, which is crucial for accelerating healing and achieving scar-free outcomes. Fig. 9As shown in AB, it was observed that on days 4 and 7 of wound healing, the pro-inflammatory cytokine TNF-α showed high expression in the control group, MS group, and FeH scaffold group, while the anti-inflammatory cytokine IL-10 was almost undetectable. In contrast, the ZnH scaffold group and the ZFBH scaffold group showed downregulation of TNF-α and upregulation of IL-10 expression. By day 16, the ZnH scaffold group and the ZFBH scaffold group showed almost no signs of inflammation or infection, only minimal levels of TNF-α, and reduced levels of anti-inflammatory factors such as IL-10. These findings suggest that the ZnH scaffold has a superior anti-inflammatory effect compared to the FeH scaffold. Zn2+ is known to play an important role in innate immunity, and previous studies have confirmed that Zn2+ can inhibit the NF-κB signaling pathway, thereby exerting anti-inflammatory activity. This chemical signal ensures a smooth transition during the inflammatory phase of wound healing. The ZFBH scaffold group had minimal inflammatory response, and its excellent anti-inflammatory properties may be attributed to the dual effects of Zn2+ release and bioelectric stimulation.
[0134] Angiogenesis is essential for early accelerated wound healing. CD31 is a marker of endothelial cells and is used to mark newly formed vascular endothelial cells. Fig.10 As shown in AB, all experimental groups showed significant CD31 expression at day 7, especially in the FeH scaffold group and the ZFBH scaffold group. These findings indicate that the wound site has a high level of vascularization and that the newly formed blood vessels promote rapid healing in the early stage. However, excessive angiogenesis in the later stage may lead to scar formation. By day 16, the expression level of vascular markers in the FeH scaffold group remained high, while the expression level in the ZFBH scaffold group decreased to the lowest, indicating that vascular degradation and remodeling occurred under the action of physical electrical stimulation. This observation highlights that the ZFBH scaffold not only promotes angiogenesis and accelerates wound healing during the inflammation and repair stages, but also promotes vascular degradation during the remodeling stage, thereby minimizing scar formation.
[0135] In summary, IHC results confirmed that the ZFBH scaffold can accelerate early wound healing in the inflammation and repair stages by applying physical electrical stimulation and chemical ion stimulation to wound defect tissue. This acceleration is achieved by activating the TGF-β / Smad / α-SMA signaling pathway, regulating inflammation (downregulating TNF-α and upregulating IL-10), and promoting angiogenesis (upregulating CD31). The early and rapid healing of the wound not only achieves the remodeling of the microenvironment, but also prevents the wound from developing into a chronic wound. In addition, in the remodeling stage of wound healing, the ZFBH scaffold inhibits the TGF-β / Smad3 / α-SMA signaling pathway and promotes the degradation and remodeling of the vascular matrix, making rapid and scar-free wound healing possible.
[0136] Example 19: In vivo toxicity assessment of ZFBH stent
[0137] After cardiac perfusion of rats in the Control group and ZFBH scaffold group (16 days), the heart, liver, spleen, lung, and kidney tissues were removed and immersed in fixative. After gradient dehydration, paraffin embedding and sectioning, H&E staining was performed and the tissues were observed under an optical microscope.
[0138] Fig.11 The experimental results showed that the ZFBH scaffold group showed no obvious visceral damage compared with the Control group, the tissue structure remained intact, the cells were arranged regularly, and there were no significant abnormalities in the nuclear-cytoplasmic ratio and cell morphology. This preliminarily indicates that the ZFBH scaffold can meet clinical safety requirements and has the potential for clinical transformation.
[0139] In summary, (1) the present invention adopts direct writing 3D printing technology to prepare a self-produced hydrogel scaffold with excellent biocompatibility, stable and long-lasting voltage output, and excellent wound healing effect without scars; it provides a suitable living environment and induction environment for cells in the wound healing site, simulates and amplifies endogenous electrical stimulation, cascade regulates the expression of genes related to wound repair, reduces the expression of pro-inflammatory factors and accelerates the vascularization of the wound site, thereby promoting scarless wound healing.
[0140] (2) The self-produced hydrogel scaffold prepared by the present invention adopts the dual properties of solid and liquid of hydrogel. Based on the solid properties, it plays a function similar to that of a battery separator, and based on the liquid properties, it acts as an electrolyte and promotes ion transport, effectively solving the problem of complex structure of traditional batteries caused by the need to construct a separator.
[0141] (3) The self-generated hydrogel scaffold prepared by the present invention has multiple repair mechanisms such as physical stimulation and chemical stimulation, including the release of zinc ions to exert anti-inflammatory effects, the release of iron ions to promote angiogenesis, the excellent antioxidant properties of each component unit, and the continuous generation of bioelectricity to promote tissue remodeling, thereby achieving scar-free wound healing, effectively avoiding the shortcomings of traditional dressings such as single function and low effect.
[0142] (4) The self-generated hydrogel scaffold prepared by the present invention constructs an adhesion layer at one end close to the wound, which prevents the dressing from falling off during use and exerts long-lasting bioelectric stimulation.
[0143] (5) The self-produced hydrogel scaffold prepared in the present invention is based on the 3D printing additive manufacturing method, which is easy to be produced quickly, in batches, on a large scale, and in a personalized manner. It has broad market prospects in the field of skin tissue repair and provides a new treatment solution for accelerating scar-free wound healing.
[0144] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A 3D printed self-produced hydrogel scaffold, characterized in that: The self-produced hydrogel support comprises an anode support and a cathode support. The anode support is obtained by 3D printing of a hydrogel containing zinc, and the cathode support is obtained by 3D printing of a hydrogel containing iron.
2. The self-produced hydrogel scaffold according to claim 1, characterized in that The concentration of zinc and iron in the hydrogel is 0.5% to 1% w / v.
3. The self-produced hydrogel scaffold according to claim 1, characterized in that The hydrogel is prepared by adding gelatin into deionized water and then adding sodium alginate.
4. The self-produced hydrogel scaffold according to claim 1, characterized in that The outside of the anode support is also wrapped with a prepolymer solution, and the prepolymer solution is prepared from dopamine, ammonium persulfate, N,N'-methylenebisacrylamide, acrylamide and tetramethylethylenediamine.
5. The self-produced hydrogel scaffold according to claim 1, characterized in that In the prepolymerization solution, the ratio of dopamine to acrylamide is 0.2-1.2% w / t; the ratio of ammonium persulfate to acrylamide is 10% w / t; the ratio of N,N'-methylenebisacrylamide to acrylamide is 0.12% w / t; and the volume ratio of tetramethylethylenediamine to water solvent is 1:
625.
6. The method for preparing the self-produced hydrogel scaffold according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) dissolving gelatin in deionized water, adding sodium alginate, and stirring evenly; (2) dividing the solution obtained in step (1) into two parts, adding zinc powder and iron powder respectively, and stirring evenly to obtain an anode support material and a cathode support material; (3) loading the anode support material and the cathode support material obtained in step (2) into a 3D printing barrel, printing them using a dual-nozzle 3D printing technology, soaking them in a calcium chloride solution, and storing them overnight to obtain an anode support and a cathode support; (4) dissolving dopamine in an alkaline aqueous solution and stirring until the solution turns brown; (5) adding ammonium persulfate, N,N'-methylenebisacrylamide, acrylamide, and tetramethylethylenediamine to the solution obtained in step (4) in an ice bath to form a brown prepolymer solution; (6) Pour the solution obtained in step (5) into the mold, immerse one end of the anode bracket obtained in step (3) in the mold, and place it in an oven at 60° C. for 30 minutes to form an adhesive ZFBH bracket.
7. The preparation method according to claim 6, characterized in that: The reaction in step (1) is carried out under heating conditions, the mass volume ratio of the zinc powder or iron powder in step (2) to deionized water is 0.5%-2% (w / v); and the concentration of the calcium chloride solution in step (3) is 1%-5% (w / v).
8. The preparation method according to claim 6, characterized in that: The pH value of the alkaline aqueous solution in step (4) is 10-14.
9. Use of the self-generated hydrogel scaffold as described in any one of claims 1 to 5, or the self-generated hydrogel scaffold prepared by the preparation method as described in any one of claims 6 to 8 in the preparation of skin repair materials and tissue engineering.
10. Use of the self-generated hydrogel scaffold as described in any one of claims 1 to 5, or the self-generated hydrogel scaffold prepared by the preparation method as described in any one of claims 6 to 8 in the preparation of a dressing for treating skin injuries.
Citation Information
Patent Citations
Aqueous high voltage zinc-anode battery
CN115699370A
Self-repairing anti-oxidation hydrogel dressing for treating oral wound and preparation method of self-repairing anti-oxidation hydrogel dressing
CN116212100A
Super capacitor structure, preparation method and application in preparation of antibacterial dressing
CN116666125A
Purpurine hydrogel / zinc self-energized electrical stimulation device for accelerating wound healing and cell proliferation and preparation method of viologen hydrogel / zinc self-energized electrical stimulation device
CN117839071A
Power unit
GB202313035D0